2019
DOI: 10.1186/s12879-019-4683-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of pulmonary non-tuberculous mycobacterial isolates in three reference centres in Belgium: a multicentre retrospective analysis

Abstract: Background/objectivesAssessing the clinical relevance of non-tuberculous mycobacteria (NTM) isolated from respiratory samples can be challenging. The epidemiology and pathogenicity of NTM species vary geographically. We aimed to outline the clinical relevance and associated radiological patterns of NTM species isolated in Belgium.MethodsWe performed a retrospective multicentre analysis of all patients identified from the laboratory database with > 1 respiratory sample growing NTM from January 2010 through Dece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…In the unadjusted analysis COPD was not associated with NTM-PD (OR 1.14, p=0.535). This finding contrasts with the findings of a study done on the Danish population (OR 2.15, p<0.0001), but is similar to the findings from a Belgian retrospective analysis (OR 1.00) [3,20]. Even though it is known that obstructive lung diseases (OLD), such as asthma and COPD, are risk factors for NTM-PD, it is unclear whether the association between NTM-PD and OLD is due to structural and/or functional abnormalities, medications used in the treatment of OLD, combination of these factors or some other factors.…”
Section: Discussioncontrasting
confidence: 58%
“…In the unadjusted analysis COPD was not associated with NTM-PD (OR 1.14, p=0.535). This finding contrasts with the findings of a study done on the Danish population (OR 2.15, p<0.0001), but is similar to the findings from a Belgian retrospective analysis (OR 1.00) [3,20]. Even though it is known that obstructive lung diseases (OLD), such as asthma and COPD, are risk factors for NTM-PD, it is unclear whether the association between NTM-PD and OLD is due to structural and/or functional abnormalities, medications used in the treatment of OLD, combination of these factors or some other factors.…”
Section: Discussioncontrasting
confidence: 58%
“…These findings are consistent with our study that identified species belonging to MAC (31%) (M. avium subspecies (32%), M. intracellulare (27%), M. yongonese (18%), M. parascrofulaceum (5%), M. paratuberculosis (2%), and M.timonense (2%)) as the most widely isolated NTM in Kenya. Other countries with similar findings include China [39]- [41], Russia [42], America [43], [44], various countries in Europe [45] and Africa [11], [20], [46]- [48]. The high infectivity rate of MAC species could be attributed to their seemingly abundant nature and distribution in different environmental sources such as water and soil, consequently increasing its ease of spread and infection to humans [20], [49].…”
Section: Discussionmentioning
confidence: 79%
“…The incidence of MAC infections is increasing continuously worldwide. Studies conducted in Belgium [ 13 ], Germany [ 14 , 15 ], South Korea [ 16 ], Japan [ 17 ], Brazil [ 18 ], and more showed the increase in incidence of MAC causing pulmonary disease, specifically MAC in the past 15 years. Most of the studies concluded that the recovery rate and infection rates of MACs were increasing in the past decade, with the highest prevalence in the elderly and individuals with existing respiratory predispositions [ 14 ].…”
Section: Resultsmentioning
confidence: 99%